Influence Of Uploading Natural Tourism Photos On Google Maps On Visiting Behavior Of Domestic Tourists Mangrove Forest - Yora Herlina; Sri Narti; Indria Indria (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
The purpose of this research is to find out the influence of uploading natural tourism photos on google maps on visiting behavior of domestic tourists by using quantitative research. Data are collected by using a questionnaire and spread that to respondents. In this research, there are two variables, free variable (x) photo upload, bound variable (Y) visiting behavior, and calculated by using SPSS 21.0. this research shows that photo upload influences the visiting behavior and from validity test, rcount rtable. This means all questions item in this research is valid. The correlation of rcount is 0,728 and higher than rtable, 0,334 means between X variable toward Y variable has positive and strong correlation means the higher number of uploads, visiting behavior will increase and can be obtained that the coefficient determination value which obtained is 0,530. It means the photo upload influence the visiting behavior for 53% while the rest 47% is influenced by other factors which are not to be researched in this research...